Desain Modul Berbasis Etnomatematika Makanan Tradisional Lepet Ketan Pada Pembelajaran Geometri - Chintia Evril; Venissa Dian Mawarsari; Iswahyudi Joko Suprayitno (Mathematics Education Study Program, 2025)
An independent learning curriculum that emphasizes culture is needed to recognize more deeply about the culture around and in Indonesia. In this era significant changes occurred in the curriculum, leading to the development of more specific skills and a focus on technology and innovation. Ethnomathematics is one of the learning approaches that relates local culture in mathematics learning. There is a need to develop teaching materials that can improve mathematical skills in students and can be easily understood in accordance with presenting social and cultural skills in their area. Researchers raised the issue of local culture, especially the traditional food Lepet Ketan to be used as a learning resource through ethnomathematical studies in it. To be clearer, the author here will examine the relationship between each form of food type and mathematical elements. This research is a type of research and development R&D (Research and Development) using the ADDIE development model. The data analysis technique used is a qualitative descriptive data analysis technique using an assessment instrument in the form of a questionnaire involving Media Experts and Material Experts Based on the data obtained through the questionnaire assessment sheet, it can be said that the module is suitable for use. The ethnomathematics-based mathematics module on the flat building material developed is Very Feasible based on validity criteria according to the validator's assessment. Based on the results of the validation of material experts, a percentage of 98%, media experts 98%.